Pheromone synthesis. Part 244: Synthesis of the racemate and enantiomers of (11Z,19Z)-CH503 (3-acetoxy-11,19-octacosadien-1-ol), a new sex pheromone of male Drosophila melanogaster to show its (S)-isomer and racemate as bioactive - Mori, K. (2014)
10.1016/j.tet.2010.06.080